Estudo da influência alimentar na etiologia da urolitíase em cordeiros - Branchini, Naiana da Silva [UNESP] (2014)
The sheep industry is a growing activity in the Brazilian livestock and plan is developed in different ways (extensive, semi-intensive, intensive). In creations, the incidence of urolithiasis has been observed. Due to this fact, the study of aspects related to the genesis, prevention, diagnosis and treatment becomes necessary and current. Incorporated to the onset of urolithiasis, power is one of the most important predisposing factors in stone formation, particularly in feedlot animals fed diets with higher volume of concentrates and little fiber. This project aims to evaluate the influence of power in the constitution of urolithiasis in sheep. Specifically, two types of diets, which differed ratio calcium/phosphorus (Ca/P) were tested. The effect of feeding on the animals was assessed by laboratory tests (serum urea and creatinine, urinalysis, concentration of phosphorus, magnesium and calcium in the blood and urine) and confirmation of diagnosis by clinical signs. 30 male sheep were used, weighing between 18 and 20kg and 4 months of age were randomly divided into 2 groups according to diet: Group 1 (n=15) - phosphorus level of 0.43% and Group 2 (n=15) - phosphorus level of 0.65%. The animals were fed the diets for 90 consecutive days and water ad libitum. Moment (M) of crop material M0 - immediately before the beginning of treatment and at 15 days intervals at M1, M2, M3, M4, M5, M6. Blood and urine samples for urinalysis, serum urea and creatinine and phosphorus concentration, Magnesium and Calcium were harvested. Animals with clinical signs urolithiasis were evaluated by physical examination, when confirmed the diagnosis, undergoing medical treatment (retrograde urethral hydropropulsion) and, when necessary, urethrostomy